Utilization of Blockchain Technology for Digital Assets Case Study Makes a Comparison Algorithm for Bitcoin and Etherium - Maesaroh, Siti; Mubarak, Roy; Yusuf, Mohamad; Daffa, Raihan Nur (Journal Collabits, 2024)
Rise of digital assets, such as cryptocurrencies, has heralded a new era in financial technology, where blockchain technology plays a fundamental role. This study conducts a comparative analysis of the blockchain algorithms underlying two of the most prominent digital assets, Bitcoin and Ethereum, to evaluate their efficacy and applicability in various use cases. Through a detailed examination of the consensus mechanisms, security features, and transaction handling capacities of both blockchains, this paper aims to provide insights into the distinct functionalities and potential scalability of each system.